Cytological differences between invasive and noninvasive or minimally invasive lung adenocarcinomas diagnosed in Japanese patients using needle biopsy specimens of pulmonary lesions ≤3 cm in diameter. Issue 7 (9th April 2019) - Matsubayashi, Jun; Miyake, Shinji; Kudo, Yujin; Shimada, Yoshihisa; Maeda, Junichi; Saji, Hisashi; Kakihana, Masatoshi; Park, Jinho; Kajiwara, Naohiro; Inoue, Shigeru; Saito, Kazuhiro; Ohira, Tatsuo; et al.
Abstract : Background: According to the WHO classification for lung cancer, adenocarcinoma in situ (AIS) and minimally invasive adenocarcinoma (MIA) have a better prognosis than invasive adenocarcinoma (IAD). However, detecting the foci of invasion in lung adenocarcinomas radiologically remains difficult. The present study examined whether or not differences in the cytological characteristics between IAD and AIS or MIA (noninvasive or minimally invasive adenocarcinomas [NMIAD]) plays a role in the differential diagnosis. Methods: Seventy surgical resection specimens of primary lung adenocarcinoma with preoperative cytology, in which several parameters were evaluated and assessed. Results: The histopathological diagnoses of surgical resection specimens were AIS in 8, MIA in 31, IAD in 31 including lepidic adenocarcinoma in 9, and papillary adenocarcinoma in 22. NMIAD had a 100% 5‐year recurrence‐free survival (RFS), while IAD had an 82.8% 5‐year RFS. The numbers of tumor cells (at ×10 magnification in 10 fields) were 60.3 ± 40.5 in IAD and 39.8 ± 28.7 in NMIAD ( P = 0.0017). A univariate analysis of cytological parameters revealed significant differences in large tumor cell clusters, three‐dimensional (3D) tumor cell clusters, and irregular nuclear contours between the two groups. The frequency of irregular nuclear contours continued to be significantly different according to a multivariate analysis. Conclusion: Large or 3D tumor cell clusters and irregular nuclear contours may be important cytological factors for distinguishing IAD from NMIAD, with the latter being potentially more important for distinguishing between the two groups.